An In-Depth Interpretive Reading of 'The Last Seeker' Diwan by Iraqi Poet Abdul AmirKhalil (مجلة إحالات, 2026)
This in-depth interpretive reading of the diwan "Sahifat Al-Mutalammis" by Iraqi poet Abdul Amir Khalil Murad aims to enter his poetic world in this collection by interpreting a set of textualthresholds with which he opens it, then by interpreting the poem "Probabilities" (Ihtimalat) with its ten poetic pulses, offering some analysis and detail. "Sahifat Al-Mutalammis and its Ten Probabilities" is written in a language that is both lavishand simple, easy and lofty, as the poetic self loads it with diverse linguistic, cognitive, poetic, andsemantic burdens in both its subjective and dramatic dimensions. The work relies on the foundations of creativity, expression, evasion, and outwitting censorship in a robust style, with aesthetic and intellectual imagery, broad imagination, and both masked and ironic paradoxes.Moreover, it skillfully employs a clear array of rich traditional references—from language, symbolism, and myth to experiences and personalities—and engages with many vast spaces:temporal, spatial, and multi-layered semantic fields.It is clearly apparent that the poetic self stands—with mastery—on the boundaries of the relationship with the self, the other, authority, society, poetry, beauty, and the contemplation ofissues such as alienation, sorrow, life and death, the individual and the group, searching for theelixir of life up close in the river of life, as well as many broad and varied dialectical, philosophical,and Sufi issues, matters of individual and national anxiety, societal concerns, and even broaderhuman issues. These ideas are laden with burning thoughts that ignite the soul and sear the heart,with their accelerating and growing impact on the reader, drawing them into the poet’s world through his calm, coherent personality, whose features are revealed and reach out to us in his poems, thresholds, and parallel texts of all kinds.